ISPD loss-of-function mutations disrupt dystroglycan O-mannosylation and cause Walker-Warburg syndrome - Willer, Tobias; Lommel, Mark; Strahl, Sabine (Nature genetics, 2012)
Walker-Warburg syndrome (WWS) is clinically defined as congenital muscular dystrophy that is accompanied by a variety of brain and eye malformations. It represents the most severe clinical phenotype in a spectrum of diseases associated with abnormal post-translational processing of α-dystroglycan that share a defect in laminin-binding glycan synthesis. Although mutations in six genes have been identified as causes of WWS, only half of all individuals with the disease can currently be diagnosed on this basis. A cell fusion complementation assay in fibroblasts from undiagnosed individuals with WWS was used to identify five new complementation groups. Further evaluation of one group by linkage analysis and targeted sequencing identified recessive mutations in the ISPD gene (encoding isoprenoid synthase domain containing). The pathogenicity of the identified ISPD mutations was shown by complementation of fibroblasts with wild-type ISPD. Finally, we show that recessive mutations in ISPD abolish the initial step in laminin-binding glycan synthesis by disrupting dystroglycan O-mannosylation. This establishes a new mechanism for WWS pathophysiology.